Efektivitas Penggunaan Limbah Cair Tahu sebagai Bahan Substitusi Pencampuran Media Tanam dalam Percepatan Pertumbuhan Miselium Jamur Tiram (Pleurotus ostreatus) - Kholida, Dina; Nofisulastri, Nofisulastri; Harisanti, Baiq Muli (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Tofu liquid waste with protein content is one of the wastes that has economic value, because the content of organic compounds and nutrients contained in it is still relatively high. Oyster mushroom is a type of wood mushroom that has a higher nutritional content than other types of wood mushrooms. Market demand for oyster mushrooms continues to increase. The need for oyster mushrooms is still relatively high and its fulfillment is still limited, therefore it is necessary to add nutrients from the outside, where tofu liquid waste can be used as an alternative growing medium for oyster mushrooms. This study aims to determine the extent to which tofu liquid waste has the potential as a substitute for mixing planting media in accelerating the growth of mycelium of oyster mushroom (Pleurotus ostreatus). This type of research is a pure experiment using a completely randomized design (CRD) using 4 treatments (0% concentration, 25%, 50%, 75% and 100%) and 5 replications. Parameters observed were the increase in length, thickness and color of the mycelium. Data were analyzed using 5% ANOVA (Analysis Of Variance) with the help of SPPS for windows program. The results of the value analysis based on the increase in length, thickness and color of the mycelium were 1.737 cm (t-count = 2.911 > t-table = 0.094); thick (t-count = 0.688 > t-table = 0.411) and white (t-count = 1.219 > t-table = 0.001).